Tahapan Perkembangan Daya Tarik Wisata Pantai Labuan Sait, Desa Pecatu, Kecamatan Kuta Selatan, Kabupaten Badung, Bali, Pasca Pandemi Covid-19 - Wulandari, Gracea Permata; Narottama , Nararya (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
Labuan Sait Beach is a tourist attraction located in Pecatu Village, South Kuta District, Badung Regency, Bali. This research is motivated by the condition of tourism facilities which are poorly maintained and accompanied by decreasing tourist visits. This research aims to determine the development of tourism in Labuan Sait Beach after the Covid-19 Pandemic. The development of Labuan Sait Beach is analyzed using the Tourism Area Life Cycle (TALC) theory. The method used in this study is a qualitative method with data collection techniques of observation, interviews, document inspection and literature study. The informants in this study were Managers of the Labuan Sait Beach Tourist Attraction, Local Communities and Tourists. The results of the study show that the tourism development of Labuan Sait Beach after the Covid-19 Pandemic is in a decline stage. This decline stage based on its characteristics is characterized by tourism support facilities that are no longer used as they should be, tourists have shown saturation with existing attractions and conditions and the level of tourist visits after the Covid-19 Pandemic has decreased. As for suggestions and recommendations based on research results, namely paying attention to the quality of tourism supporting facilities by carrying out maintenance and improvements to facilities, increasing promotions, especially through social media, increasing cooperation between managers, government and the community. In addition, tourists are expected to participate in paying attention to tourism supporting facilities and maintaining the cleanliness of the environment and respecting local community.